Apakah Sistem Pengendalian Manajemen Mampu Mengukur Efisiensi dan Efektifitas Kinerja Rumah Sakit? (Journal of Hospital Management, 2019)
This study examines the issue that contingency behavior does not yet have a comprehensive theoretical and empirical study in the institutional relationship between management control systems and hospital organization performance in a situational perspective in the application of good hospital governance. The purpose of this study is to analyze the significant influence together between environmental uncertainty, information technology, and hospital management control systems on hospital organizational performance. This research uses survey research methods with an explanatory approach to causality research. The unit of analysis is medical and non-medical employees of Aini Eye Hospital Prof. Isak Salim. Time horizon uses cross section. The sampling technique is saturated sampling. This study uses Path Analysis, the number of samples collected was 88 samples. The results showed that there was a significant simultaneous influence between environmental uncertainty, information technology, and hospital management control systems on organizational performance; there is a positive influence of environmental uncertainty on the Management Control System; there is a positive influence of information technology on Hospital Management Control Systems; there is a positive influence of the Management Control System on Hospital Organizational Performance; there is a positive influence of Environmental Uncertainty on Hospital Organizational Performance; and there is a positive influence of Information Technology on Organizational Performance. The research findings are that the hospital carries out a budget preparation process with an optimistic approach in determining organizational targets. So that the hospital is able to perform efficiency performance, although it does not produce effective performance, hospital sustainability in its operational activities.Keyword: environmental uncertainty, information technology, management control systems, organizational performance of hospitals